KONSTRUKSI GELOMBANG KEJUT DAN GELOMBANG MENJARANG PADA ARUS KENDARAAN DI LALU LINTAS - Maya Sari Syahrul; Nurweni Putri (LPPM Universitas Bina Bangsa, 2023)
In nonlinear conservation laws, there is a possibility of intersecting characteristic lines or even regions that are not traversed by characteristic lines. In regions where there are two or more characteristic lines, a gradien catastrophic phenomenon can occur, resulting in the emergence of a breaking time, thus a weak solution of the nonlinear conservation law is considered. Such a weak solution is capable of producing shock wave solutions at the breaking time. Additionally, there are rarefaction wave solutions for regions that do not have characteristics. The construction of shock wave and rarefaction wave solutions can be observed in a case study in traffic flow, specifically before and after a traffic light turns red. Shock waves are observed in the flow of vehicles before the red light, while rarefaction waves occur when the red light changes to green